An introduction to fluid dynamics - Batchelor, G. K. (George Keith) (Cambridge : Cambridge University Press, 2000)
First published in 1967, Professor Batchelor's classic text on fluid dynamics is still one of the foremost texts in the subject. The careful presentation of the underlying theories of fluids is still timely and applicable, even in these days of almost limitless computer power. This re-issue should ensure that a new generation of graduate students see the elegance of Professor Batchelor's presentation.
The physical properties of fluids -- Kinematics of the flow field -- Equations governing the motion of a fluid -- Flow of a uniform incomprehensible viscous fluid -- Flow at large Reynolds number : effects of viscosity -- Irrotational flow theory and its applications -- Flow of effectively inviscid fluid with vorticity.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Fluid dynamics